Burn Case Prevalence In Dr Kariadi General Hospital Semarang From 2012 to 2014 - Tanuwijaya, Lucretya Yeniwati (Jurnal Plastik Rekonstruksi, 2020)
Background: Burns is a type of trauma that requires treatment and rehabilitation, which is still difficult and requires perseverance, a high amount of costs, and trained and skilled personnel. Morbidity and mortality of burns are relatively high, especially in developing countries where burn prevention and treatment systems are inadequate. The prevalence of burns is expected to be an advantage for the development of science in further research and could help clinicians prevent and curative burn care efforts. Method: The study subjects were burned patients examined and hospitalized at Dr. Kariadi General Hospital, Semarang. Data from each sample's clinical examination results were then collected to be described based on gender, age, burns degree criteria, and etiology of burns. Results: The total sample obtained was 72 samples, including 61 patients (85.53%) with new burns and 11 non-emergency patients (14.47%). From a total of 61 new burn patients, eight female patients (13.11%) and 53 male patients (86.89%) were obtained; 10 patients (16.40%) were children (0-18 years), 50 (81.96%)were adults (18-65), and one patient (1.64%) belonged to geriatric (> 65 years) ); based on the degree of the burns, seven patients (11.48%) had a moderate degree and 54 patients (88.52%) had a severe degree; there were 28 patients (45.90%) who suffered burns caused by fire, 20 patients (32.79%) due to electricity, six patients (9.84%) caused by scald, and seven patients (11.47 %) with an unknown cause. Of the 61 new burn patients, there were five patients (8.20%) who died. Conclusion: Burn prevalence in Dr. Kariadi General Hospital, Semarang in 2012-2014 are mostly experienced by men, adults, with severe burn criteria, with the most common etiology is fire.